Physical Fitness Changes in Girls from the 11th Grades Promoting their Physical Self-Development and Training their Least Developed Physical Qualities (Baltic Journal of Sport and Health Sciences, 2018)
The aim of the research was to determine the changes in physical ﬁ tness of girls from the 11th grades promoting their self-education and training their least developed physical qualities.The sample of the research included one experimental and one control group, each consisting of 24 female subjects (n = 48) from the X school in Klaipėda. The subjects of each group were selected using the random sampling method. Each group had two weekly PE lessons according to the Lithuanian General Physical Education Curriculum.Testing physical ﬁ tness based on the guidelines of the Euroﬁ t tests was performed in the middle of September, 2003 and the middle of April, 2004. The pedagogical experiment lasted for 7 months. To determine physical ﬁ tness of subjects, the Euroﬁ t tests were used in the following order: sit-and-reach, standing broad jump, sit-ups, bent arm hang, shuttle run 10 × 5 metres. The results were assessed according to the National Euroﬁ t Reference Scales.It was found that physical ﬁ tness of girls from the 11th grades was low: according to the Lithuanian Euroﬁ t Reference Scales, the test score in standing broad jump was 3, the test score in sit-and-reach, sit-ups and shuttle run 10×5 m was 4 and the test score in bent arm hang was 5. In the ﬁ rst tests it was determined that the least developed traits in subjects were the strength of their leg and abdominal muscles and suppleness. For the experimental group, the physical education programme was modiﬁ ed with greater focus on training strength and suppleness. PE lessons for the experimental group included training pupils’ awareness about PE and promoting of self-education. For this reason, the girls were taught to calculate and evaluate their body mass index, they had theoretical lessons about the importance of strength and suppleness as physical qualities and methods how to train them, the importance of exercising, methods of stretching and personal exercising, self-assessment of physical condition. The programme designed to promote the need for self-development and to train strength and suppleness had a po-sitive effect on physical ﬁ tness changes in girls: most of physical qualities increased signiﬁ cantly in girls from the experimental group.Keywords: physical fitness, physical qualities, physical self-development.